MENYIBAK AJARAN SOSIAL GEREJA PAUS FRANSISKUS DI MASA PANDEMI DALAM PERSPEKTIP HIDUP SOSIAL SEBAGAI RUMAH BERSAMA - Benedikta Yosefina Kebingin (Jurnal Reinha, 2021)
This research is intended to examine the social teachings of the Church of Pope Francis during the pandemic. It is interesting to study because the social teachings of the Church which has been rolling from time to time since 1891 covers documents classified as the social teachings of the Church; while the catechesis of Pope Francis during the pandemic in nine themes was directly entitled "The Social Teachings of the Church of Pope Francis in the Pandemic Era" which is a unitary theme immediately given the title as a social teaching of the Church (during the pandemic). For this reason, in order to ascertain the distinctive color of Pope Francis' teachings, the author re-examines the documents of the Social Teachings of Church that have existed since Pope Leo XIII, Rerum Novarum to John Paul II, Laborem Exercens. For that, the research method used is document research. From the results of the research conducted, it is concluded that the perspective of social life as a common house is an appendix to the entire teaching of Pope Francis in this document.